2022
DOI: 10.3390/bios12110963
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Platform Revealing Interactions between Leukocytes and Cancer Cells on Topographic Micropatterns

Abstract: Immunoassay for detailed analysis of immune−cancer intercellular interactions can achieve more promising diagnosis and treatment strategies for cancers including nasopharyngeal cancer (NPC). In this study, we report a microfluidic live−cell immunoassay integrated with a microtopographic environment to meet the rising demand for monitoring intercellular interactions in different tumor microenvironments. The developed assay allows: (1) coculture of immune cells and cancer cells on tunable (flat or micrograting) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, coculturing different cell types on microfluidic devices such as cancer cells and immune cells allows for the study of complex cell–cell interactions that are important in the development of cancer immunotherapies. Cui et al introduced a versatile microfluidic immunoassay that integrates microtopographic cell-culture substrates with a microbeads-based immunofluorescence assay for rapid and sensitive analysis . Parlato et al reported a microfluidic platform composed of five parallel channels capable of assessing the guided efficient motion of Interferon-α-conditioned dendritic cells toward cancer cells and subsequent phagocytosis .…”
Section: Phenotypic Screening Techniques Enabled By Microfluidic Plat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, coculturing different cell types on microfluidic devices such as cancer cells and immune cells allows for the study of complex cell–cell interactions that are important in the development of cancer immunotherapies. Cui et al introduced a versatile microfluidic immunoassay that integrates microtopographic cell-culture substrates with a microbeads-based immunofluorescence assay for rapid and sensitive analysis . Parlato et al reported a microfluidic platform composed of five parallel channels capable of assessing the guided efficient motion of Interferon-α-conditioned dendritic cells toward cancer cells and subsequent phagocytosis .…”
Section: Phenotypic Screening Techniques Enabled By Microfluidic Plat...mentioning
confidence: 99%
“…Cui et al introduced a versatile microfluidic immunoassay that integrates microtopographic cell-culture substrates with a microbeads-based immunofluorescence assay for rapid and sensitive analysis. 26 Parlato et al reported a microfluidic platform composed of five parallel channels capable of assessing the guided efficient motion of Interferon-αconditioned dendritic cells toward cancer cells and subsequent phagocytosis. 27 Tu et al developed a microfluidic device that allows for comprehensive analysis of immunocyte heterogeneity during interactions with tumor cells at the single-cell level, uncovering the effects of immune checkpoint blockade in cancer.…”
Section: Phenotypic Screening Techniques Enabledmentioning
confidence: 99%
“…29 Apart from evaluating the cytokine secreted by a single type of cell, studies for evaluating interactions between multiple types of cells were also presented. 30 The antibody-assisted enrichment 31 and immunofluorescence 32 to detect cytokines were also proven feasible in the scenario of coculturing multiple kinds of cells in microfluidic devices.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…Microfluidics involves the examination and control of minute quantities of fluids, typically in the microliter or nanoliter range. This field has gained significant prominence in research due to its diverse applications in areas like biotechnology, pharmaceuticals, diagnostics, lab-on-chip (LOC), separation and isolation of circulating tumor cells, sperm sorting, and bacteria or algae detection [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The integration of microscale structures on a single chip has revolutionized research across various domains by enabling the swift manipulation, analysis, and distribution of small samples.…”
Section: Introductionmentioning
confidence: 99%